A Way to Boost the Impact of Business on 2030 United Nations Sustainable Development Goals: Co-creation With Non-profits for Social Innovation - Díaz-Perdomo, Yolanda; Álvarez-González, Luis Ignacio; Sanzo-Pérez, María José (Frontiers in Psychology, 2021)
The evolution of Corporate Social Responsibility is forcing firms to adopt a new business approach based on combining competitiveness improvement with societal well-being. Considering the existence of huge social and environmental challenges, independent actions undertaken by each of the societal actors with only their own resources reveal clearly insufficient to address them. A way firms can encourage the achievement of the Sustainable Development Goals is by partnering with stakeholders, and particularly by developing strategies of co-creation with nonprofits. This study assesses the effects of business-nonprofit value co-creation on both the partners’ organizational performance, and the social results linked to the Sustainable Development Goals. The results derived from a quantitative-based research with 205 Spanish nonprofits show a positive effect of co-creation on indicators at the micro (individuals), meso (both organizations), and macro (society) levels. Furthermore, positive indicators at the micro and macro levels have a positive influence on the partners’ performance.